2002
DOI: 10.1161/hc0802.104503
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of Carvedilol, Metoprolol, and Propranolol on Left Ventricular Remodeling After Coronary Stenosis or After Permanent Coronary Occlusion in Rats

Abstract: Background-Although carvedilol attenuates left ventricular (LV) remodeling in coronary occlusion-reperfusion, it is not known whether it attenuates ischemic LV remodeling because of coronary stenosis (CS) or permanent coronary occlusion (CO). Methods and Results-We administered a vehicle, carvedilol, propranolol (2, 10, and 30 mg/kg per day, each), metoprolol (6, 30, and 90 mg/kg per day), or bunazosin (0.2 and 1 mg/kg per day), orally for 12 weeks to a total of 608 rats with CS or CO. In these groups and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
46
1
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 17 publications
5
46
1
4
Order By: Relevance
“…6 As the purpose of this study was to compare the efficacy of different AR antagonists in suppressing LV remodeling secondary to hypertension, the prerequisite for a chosen drug is to lower blood pressure to a normal level. The drug doses were determined by referring to previous studies on animal models of LV remodeling [7][8][9][10] and by a preliminary study in which the drug doses were increased gradually from a low dose until the systolic blood pressure (SBP) in each drug-treated group reached the level of SBP as that of WKY rats. Our preliminary results showed that bisoprolol, propranolol and carvedilol at a dose of 2 mg kg À1 per day, 6 mg kg À1 per day and 6 mg/kg/day, respectively, were effective in normalizing SBP in SHR and thus, these doses were finally chosen for comparing the therapeutic effects of bisoprolol, propranolol and carvedilol in suppressing LV remodeling in SHR.…”
Section: Animal Model and Experimental Protocolmentioning
confidence: 99%
“…6 As the purpose of this study was to compare the efficacy of different AR antagonists in suppressing LV remodeling secondary to hypertension, the prerequisite for a chosen drug is to lower blood pressure to a normal level. The drug doses were determined by referring to previous studies on animal models of LV remodeling [7][8][9][10] and by a preliminary study in which the drug doses were increased gradually from a low dose until the systolic blood pressure (SBP) in each drug-treated group reached the level of SBP as that of WKY rats. Our preliminary results showed that bisoprolol, propranolol and carvedilol at a dose of 2 mg kg À1 per day, 6 mg kg À1 per day and 6 mg/kg/day, respectively, were effective in normalizing SBP in SHR and thus, these doses were finally chosen for comparing the therapeutic effects of bisoprolol, propranolol and carvedilol in suppressing LV remodeling in SHR.…”
Section: Animal Model and Experimental Protocolmentioning
confidence: 99%
“…38 In contrast, Yaoita et al explain the attenuation of LV remodeling with propranolol and metoprolol by reduction of heart rate and systolic blood pressure. 41 Furthermore, Zhu et al have showed that in a rat model ischemia/reperfusion injury, metoprolol produced cardioprotection via hemodynamic effects. 42 More recently, Omerovic et al suggest that metoprolol attenuates post-infarct structural remodeling, without concomitant improvement in myocardial energy metabolism and function in rats with chronic congestive heart failure, 43 but authors could not completely explain which effect is responsible from this improvement.…”
Section: Discussionmentioning
confidence: 99%
“…18) Since supraventricular tachyarrhythmias leading to atrial fibrillation can affect cardiac function, carvedilol's effect on I K and I Ca observed in our study, at least in part, may be responsible for the good prognosis in various clinical trials. Of course, carvedilol has a number of ancillary activities, including antioxidant, anti-inflammatory, and antiapoptotic properties in addition to the well-known properties, [2][3]5) and hence, some unknown antiarrhythmic activities might exist. Further studies will be required to elucidate these points.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its nonselective β-adrenergic blocking effect, it also has α 1 adrenergic blocking actions, 1) antioxidant properties, 2,3) Ca 2+ blocking effects, 4) and inhibitory effects on cardiac remodeling and myocyte apoptosis. [5][6][7] Recently, this agent has attracted increasing attention among cardiologists following positive outcomes in various clinical trials.…”
mentioning
confidence: 99%